Usability of the CERDASIA Application (Check the Development, Nutrition, Children and Mental Health of Indonesian Adolescents) at the Sukawarna Community Health Center - Alfina Salsabila; Anida Aulia; Ariel Sanria; Arwinda Agustin; Ashila Rahma; Cici Amelia; Dina Amalia; Kharisma Adinda; Linlin Lindayani (STIKep PPNI Jawa Barat, 2026)
Background: Early childhood growth and development monitoring and adolescent mental health are important components of promotive and preventive efforts in primary health care. However, conventional methods are often ineffective in reaching parents and adolescents sustainably. The use of digital technology is an innovative alternative to improve access to information and the quality of health services. Objective: This study aims to evaluate the usability of the CERDASIA (Cek Pengembangan, Gizi, dan Kesehatan Anak Remaja Indonesia) application as a supporting medium for monitoring child growth and development and adolescent mental health. Method: This study used a descriptive design with a cross-sectional approach. Respondents consisted of parents of children aged 0–5 years and adolescents in the Sukawarna Community Health Center (Puskesmas) working area. Usability evaluation was conducted using the System Usability Scale (SUS) and a time completion test to assess ease of use, efficiency, and user experience. Data were analyzed descriptively. Results: The average SUS score showed a good usability category, indicating that the CERDASIA application is easy to use, has clear navigation, and is able to increase user satisfaction. Conclusion: The CERDASIA application has good usability and has the potential to become a nursing technology innovation in supporting child growth and development monitoring and adolescent mental health